Optimization of nucleic acid scaffold design using fluorescence measurements. (28th January 2019) - Anderson, Jessica; Moss, McKenze; Nguyen, Nancy; Hughes, Natalie; Gee, Amira; Ali, Mehnaaz F.
Abstract: The current work focuses on optimizing aptamer scaffolds that are tailored to allow for the formation of binding pockets for both a redox active signaling molecule and the target miR-92a. These newly designed allosteric nucleic acid systems are studied for efficacy to undergo a target based conformational switch. Two hairpin scaffolds were designed with differing stem stabilities and were explored using fluorescence quenching measurements. The dose dependent data for the detection of miR-92a shows the importance of scaffold design where the stability of the intra-molecular hairpin structure has to be optimized for target binding. Additional experiments explored the selectivity of the aptamer scaffolds in the presence of competing miR's and mismatched sequences. These results provide an important precursor to constructing nucleic acid scaffolds for the detection of miR's using label-free redox signaling.